Environmental, social, and governance perspectives on economic development in Asia - Barnett, William A.; Sergi, Bruno S. (Emerald Publishing Limited, 2021)
This volume of the International Symposia in Economic Theory and Econometrics explores the latest economic and financial developments in Asia. Chapters cover a range of topics such as the impact machine learning models have on forecasting, the levels and effects of financial literacy of farmers in Thailand, as well as the need to prioritise increasing employee engagement for sustainability. These peer-reviewed papers touch on a variety of timely, interdisciplinary subjects such as corporate social responsibility and the effects of public policy. Environmental, Social, and Governance Perspectives on Economic Development in Asia also includes empirical studies in financial economics and public governance. For example, one chapter considers the influence of green supply chain integration and environmental uncertainty on performance in Indonesia, while another empirically studies Banking Development and Household Welfare in Thailand. Together, ISETE 29 volume A, is a crucial resource of current, cutting-edge research for any scholar of international finance and economics.
Includes index.
Keywords: Economic development -- Asia.; Asia -- Economic conditions -- 21st century.; Business & Economics -- Development -- Economic Development.; Development economics & emerging economies.; elektronické knihy; electronic books